The Importance of Student Leagues on Medical Training in Neurosurgery and Residency Choice - Moraes, Daniela Macêdo de; Braga, Vinícius Lopes; Riechelmann, Guilherme Salemi; Cavalheiro, Sérgio (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2018)
Introduction Neurological and neurosurgical disorders are highly prevalent in Brazil. The initial management is performed by general practitioners, showing the importance of theoretical and practical studies of neurology and neurosurgery during undergraduate medical courses.Objective Describe the choices of medical specialty by members of a neurosurgery student league and investigate the existence and composition of neurology and/or neurosurgery courses and neuro-leagues in medical schools in Brazil. Methods We surveyed, in person or through social networks, all medical students who were members of the Neurosurgery Student League of Escola Paulista de Medicina (EPM) from 2007 to 2015 on the completion of their course and residency chosen. An online form was also submitted to all the medical schools registered with the Federal Council of Medicine (Conselho Federal de Medicina [CFM])Results and Discussion Fifty-seven medical graduates had participated in the Neurosurgery Student League of EPM. Out of these, 45 have completed their undergraduate courses; 6 have undergone neurosurgery and 5 neurology. We obtained responses from 128 out of the 173 medical schools affiliated with the CFM. A total of 91% of the schools responded that they have a structured neurology course. These courses are divided as into: 32 exclusively theoretical, with 12 addressing neurosurgery and 84 are theoretical-practical, with 51 addressing neurosurgery. Structured neurosurgery courses were only present in 19% of the faculties, half of which are theoretical only. Neurosciences leagues were present in 66% of the universities.Conclusions It was noted that neurology and neurosurgery student leagues in 66% of the medical schools in Brazil is, many times, used to supplement theoretical-practical content that should have been addressed at undergraduate level. Unfortunately, only 9.5% of the medical schools include a theoretical-practical neurosurgery course in their curriculum, a fact that is concerning due to the high prevalence of neurologic diseases in the Brazilian population.
Keywords: neurosurgery; educational assessment; undergraduate medical education; student leagues; neurology